Experts' perspectives on the role of medical marijuana in oncology: A semistructured interview study. Issue 8 (26th January 2017) - Braun, I.M.; Meyer, F.L.; Gagne, J.J.; Nabati, L.; Yuppa, D.P.; Carmona, M.A.; Burstein, H.J.; Suzuki, J.; Nayak, M.M.; Martins, Y.
Abstract: Background: Expansion of medical marijuana (MM) laws in the United States may offer oncology new therapeutic options. However, the scientific evidence for MM remains in infancy. This study qualitatively explored professional opinion around the role of MM in cancer care. Methods: Semistructured interviews were administered to a sample of individuals with expertise at the interface of MM and oncology nationally. Key informant criteria included an oncologic clinical or research background and any of the following: publications, research, or lectures on cannabinoids or cancer symptoms; involvement in the development of MM dispensaries or legislation; and early adoption of state MM certification procedures. A gold standard, grounded, inductive approach was used to identify underlying themes. Results: Participants (N = 15) were predominantly male, in their sixth decade, working in academic settings. Themes ranged from strong beliefs in marijuana's medical utility to reservations about this notion, with calls for expansion of the scientific evidence base and more stringent MM production standards. All participants cited nausea as an appropriate indication, and 13 of 15 pain. Over one‐third believed MM to have a more attractive risk profile than opioids and benzodiazepines. Conclusions: Expert opinion was divided between convictions in marijuana's medicinal potential and guardedness in this assertion, with no participant refuting MM's utility outright. Emergent themes included that MM ameliorates cancer‐related pain and nausea and is safer than certain conventional medications. Participants called for enhanced purity and production standards, and further research on MM's utility.